Analisis Profesionalisme Birokrasi terhadap Kinerja Pegawai Pada Sekretariat DPRD Provinsi Sumatera Utara - Syafrida Yanti; Marlon Sihombing; Dumasari Harahap (Universitas Medan Area, 2022)
This study aimed to undergo an analysis on the Profesionalism of the Government ApparatusÂ Â in implementation governmental tasks, development and society education. The study applied a qualitative method using a phenomenological approach. The informant selection is performed by purposive sampling tecnique. The Informant consist of the member of Province of North Sumatra, Head of Subsection and Staff of The Secretariat of The DPRD Province of North Sumatra. In addition to these, the study also involved concerned institution. Instrument of the study comprised the writer himself and data collection by in depth interview, documentation, and field observation, whereas technique of data analysis used a taxonomy analysis. Profesionalism of the government apparatus to be assessed consisted of responsiveness and inovation performed by the staff of Secretariat of The DPRD Province of North Sumatra in their governmental tasks implementation, development and society education as well as service accomodation to ythe citizens. In general, profesionalism of the government apparatus from the viewpoint of the apparatus responsiveness and inovation at Secretariat of The DPRD Province of North Sumatra Regency still lacked of quality. Such condition was affected by vision and mission of the organization and responsibility of the organizational structure, leadership, and reward that din not meet the objective of the organization. They should have been given a serious attention for the purpose of determining organizational goals.